K / O co-doped and cyano-grafted graphite phase carbon nitride material as well as preparation method and application thereof

By introducing K/O co-doping and cyanograft structures into graphite phase carbon nitride materials, the problem of photogenerated carrier recombination and insufficient active sites of the photocatalyst is solved, and efficient photocatalytic hydrogen peroxide production effect is achieved.

CN119565655APending Publication Date: 2025-03-07QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202411423682.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing graphite phase carbon nitride (g-C3N4) photocatalysts have problems with photogenerated carrier recombination, limited photo collection efficiency and insufficient active sites, resulting in low efficiency in H2O2 production.

Method used

By introducing K/O co-doping and cyanograft structures into graphite phase carbon nitride materials, a three-defect structure of K-N bridge, C-O-C bond and cyano group are formed, which promotes the transmission and separation of photogenerated electrons, broadens the light absorption range, and improves the number and efficiency of active sites.

Benefits of technology

The photocatalytic effect of the photocatalyst is significantly improved, the utilization rate of sunlight is enhanced, and the photocatalytic hydrogen peroxide production capacity is shown in both visible and ultraviolet light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a K / O co-doped and cyano-grafted graphite phase carbon nitride material as well as a preparation method and application thereof. The material comprises three defect types, namely a C-O-C bond formed by a C-N = C bond in an oxygen substituted triazine skeleton, potassium ions existing between layers and cyano groups generated by protonation of amino groups at the edge. According to the material disclosed by the invention, K ions are doped into the g-C3N4 layer to form K-N bridge connection between layers, the material can be used as an electron channel to effectively accelerate electron migration, cyano groups at the edge have relatively strong electron-withdrawing capability and can be used as sites for adsorbing hydrogen ions, and introduced oxygen can be used as active sites for producing H2O2. The three components cooperate with each other to effectively promote transmission of photo-induced electrons and separation of photo-induced electron hole pairs, so that the photocatalytic effect is remarkably improved, and the photocatalyst is an efficient photocatalyst with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a K / O co-doped, cyano-grafted graphite phase carbon nitride material and a preparation method and application thereof, belonging to the technical field of photocatalyst hydrogen peroxide production. Background Art

[0002] With the unrestrained exploitation and utilization of fossil energy by humans, not only serious energy shortages have been caused, but also a series of environmental pollution problems have been accompanied. Therefore, it is necessary to develop alternative energy sources to effectively solve the above problems. Photocatalytic technology is based on the redox ability of photocatalysts under light conditions, so as to achieve the purpose of purifying pollutants, material synthesis and conversion. At present, the industrial production of hydrogen peroxide is mainly through large-scale centralized anthraquinone cycle method. The problem with this method is that its energy comes from fossil fuels, which will emit a large amount of carbon dioxide and produce a lot of organic waste and by-products. Usually, the photocatalytic redox reaction uses semiconductors as catalysts and light as energy to reduce oxygen to produce hydrogen peroxide or oxidize water to produce hydrogen peroxide. Therefore, photocatalytic technology, as an efficient, safe and environmentally friendly environmental purification technology, has been recognized by the international academic community for improving indoor air quality.

[0003] Among many photocatalysts, graphitic carbon nitride (g-C3N4) has great potential in producing H2O2 due to its suitable bandgap width and reasonable conduction band and valence band position. However, the photocatalytic activity of pristine g-C3N4 suffers from serious problems of photogenerated carrier recombination, limited light collection efficiency, and insufficient active sites due to the strong Coulomb interaction of its intrinsic singlet Frenkel excitons. On the one hand, the weak van der Waals interaction between adjacent layers of g-C3N4 limits electron coupling and has a negative impact on electron transfer. Therefore, it is very important to design specific coordination bonds between g-C3N4 layers as interlayer bridges and construct charge transfer channels between adjacent layers to improve the production of H2O2. It is reported that the introduction of alkali metal-nitrogen coordination (such as KN bonds) in the g-C3N4 layer can form interlayer bridges as electron channels, thereby effectively accelerating electron migration. For example, patent document CN118454714A discloses a potassium-phosphorus co-doped graphite phase carbon nitride material and a preparation method thereof. The obtained potassium-phosphorus co-doped graphite phase carbon nitride material exhibits enhanced light absorption performance, and the light absorption range is broadened to the near-infrared light region. This is attributed to the introduction of a sub-band gap when the K and P elements are doped, so that it can absorb photons with energy lower than its intrinsic band gap, allowing more photogenerated carriers to participate in the reaction, effectively promoting the photocatalytic oxygen reduction reaction.

[0004] Although the introduction of alkali metal nitrogen coordination in g-C3N4 can enhance electron migration, the activation of O2 by g-C3N4 is still weak due to the slow kinetics of surface redox reactions. -Therefore, while promoting charge separation through interlayer bridging, the introduction of active sites also plays a vital role in enhancing the surface reaction kinetics. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a K / O co-doped, cyanide-grafted graphite phase carbon nitride material and a preparation method and application thereof.

[0006] The K / O co-doped, cyanide-grafted graphite phase carbon nitride material of the present invention has three defects, which effectively promote the transmission of photogenerated electrons and the separation of photogenerated electron-hole pairs, broaden the light absorption range, and significantly improve the photocatalytic effect. It is an efficient photocatalyst with excellent performance, a simple preparation method and a low production cost.

[0007] The present invention is achieved through the following technical solutions:

[0008] The first object of the present invention is to provide a K / O co-doped, cyano-grafted graphite-phase carbon nitride material.

[0009] A K / O co-doped, cyanide-grafted graphite phase carbon nitride material has a lamellar structure in microstructure, K ions form KN bridges between lamellar layers, oxygen replaces CN=C bonds in triazine skeletons to form COC bonds, and amino groups at the edges of carbon nitride are protonated to generate cyanide groups.

[0010] The present invention dopes K ions into the g-C3N4 layer to form a KN bridge between the layers, which can serve as an electron channel to effectively accelerate electron migration. The cyanide group at the edge has a strong electron-withdrawing ability and can serve as a site for adsorbing hydrogen ions. The introduction of oxygen can serve as an active site for producing H2O2.

[0011] The second object of the present invention is to provide a method for preparing the above-mentioned K / O co-doped, cyanide-grafted graphite-phase carbon nitride material.

[0012] The preparation method of the above-mentioned K / O co-doped, cyano-grafted graphite phase carbon nitride material comprises the following steps:

[0013] (1) adding urea to deionized water and stirring to dissolve, then adding potassium hydroxide and stirring to prepare a first mixed solution;

[0014] (2) drying the first mixed solution of step (1) and cooling it to room temperature to prepare a first solid mixture;

[0015] (3) calcining and cooling the solid mixture obtained in step (2) to room temperature to obtain a second solid mixture;

[0016] (4) Washing the second solid mixture in step (3) with water, and then drying the precipitate after centrifugal washing to obtain a K / O co-doped, cyanide-grafted graphite phase carbon nitride material.

[0017] Preferably according to the present invention, in step (1), the mass volume ratio of urea to deionized water is (10-20):30, in units of g / mL.

[0018] Preferably according to the present invention, in step (1), the mass ratio of urea to potassium hydroxide is (10-20): (0.3-1).

[0019] Further preferably, in step (1), the mass ratio of urea to potassium hydroxide is (10-20):(0.3-0.7).

[0020] Most preferably, in step (1), the mass ratio of urea to potassium hydroxide is (10-20):0.5.

[0021] Preferably according to the present invention, in step (1), the stirring is performed at room temperature for 10-30 min.

[0022] Preferably according to the present invention, in step (2), the drying temperature is 75-85° C. and the drying time is 10-20 h.

[0023] Preferably, according to the present invention, in step (2), before drying, the mixture is first transferred to a 100 mL crucible and sealed with dust-free paper to control the evaporation rate of the aqueous solution.

[0024] Preferably, according to the present invention, in step (3), the calcination is performed by placing the mixture in a muffle furnace at 500-600° C. for 1-3 hours, cooling the mixture to 450-550° C. for 1-3 hours.

[0025] Preferably, according to the present invention, in step (3), the calcination is performed by placing the mixture in a muffle furnace at 550° C. for 2 hours, cooling the mixture to 450-550° C. and maintaining the mixture for 2 hours.

[0026] Preferably according to the present invention, in step (4), the drying temperature is 75-85° C. and the drying time is 10-20 h.

[0027] In the preparation process of the present invention, urea is added to deionized water, stirred and dissolved, and then potassium hydroxide is added. Through the interaction between potassium metal doping and urea precursor, the oxygen atoms in the urea molecule are incorporated into the carbon nitride skeleton. In addition, under KOH heat treatment, the terminal amino group is protonated to produce cyanide, and potassium ions are intercalated between carbon nitride layers. The three cooperate with each other to effectively inhibit the recombination of electrons and holes. It has a high photocatalytic effect of producing hydrogen peroxide under visible light, effectively improving the utilization rate of sunlight. At the same time, the structure of three defects can enhance the photocatalytic effect of carbon nitride nanosheets and make up for the shortcomings of the carbon nitride sheet structure.

[0028] Application of the above K / O co-doped, cyanide-grafted graphite phase carbon nitride material in photocatalytic production of hydrogen peroxide.

[0029] The K / O co-doped, cyanide-grafted graphite phase carbon nitride material of the present invention is a triple-defect catalyst having oxygen atoms doped into the carbon nitride skeleton, cyanide groups at the edges, and potassium ions intercalated between carbon nitride layers, and has a highly efficient hydrogen peroxide production capability.

[0030] According to the preferred embodiment of the present invention, the specific application method is as follows:

[0031] Using LED as the light source, the K / O co-doped, cyano-grafted graphite phase carbon nitride material is added to water containing isopropanol, and treated in the dark under the condition of continuous oxygen bubbling to achieve oxygen adsorption equilibrium, and then illuminated to achieve photocatalytic production of hydrogen peroxide.

[0032] Preferably according to the present invention, the mass volume ratio of the K / O co-doped, cyanide-grafted graphite phase carbon nitride material to the water containing isopropanol is (4-8):30, the unit is mg / mL, the mass concentration of isopropanol in the water containing isopropanol is 10%, the dark treatment time is 20-40min, the illumination time is 20-70min, and the light source is ultraviolet light or visible light.

[0033] The technical features and advantages of the present invention are as follows:

[0034] 1. From the preparation process, first of all, the present invention controls the solidification rate of the solution to solid, and then calcines twice under high temperature conditions to obtain the oxygen-substituted triazine skeleton CN=C bond to form COC bond, potassium ions exist between layers, and the edge amino groups are protonated to form a cyanide triple defect structure to enhance the visible light photocatalytic effect of carbon nitride nanosheets, achieving excellent photocatalytic effects under ultraviolet light and visible light, thereby broadening the scope of sunlight utilization and improving the photocatalytic effect.

[0035] 2. In terms of performance, after testing of the specific implementation methods of the present invention, the K / O co-doped, cyanide-grafted graphite-phase carbon nitride material prepared by the present invention has been greatly improved compared with simple carbon nitride nanosheets, both in terms of the amount of hydrogen peroxide produced by photolysis of water and in terms of the rate of hydrogen peroxide produced by photolysis of water, which proves the significant advantages of the K / O co-doped, cyanide-grafted graphite-phase carbon nitride material of the present invention in the application of photocatalytic production of hydrogen peroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings in the specification, which constitute a part of the present application, are used to provide further understanding of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.

[0037] Figure 1This is a high-magnification transmission electron microscopy image of the K / O co-doped, cyanide-grafted graphite-phase carbon nitride material prepared in Example 2 of the present invention.

[0038] Figure 2 This is a graph showing the amount of hydrogen peroxide produced by photocatalysis of the K / O co-doped, cyanide-grafted graphite-phase carbon nitride material prepared in Examples 1-3 of the present invention under LED visible light irradiation.

[0039] Figure 3 This is a graph showing the photocatalytic hydrogen peroxide production rate of the K / O co-doped, cyanide-grafted graphite-phase carbon nitride material prepared in Examples 1-3 of the present invention under LED visible light irradiation.

[0040] Figure 4 This is a data diagram of oxygen activation active sites of the K / O co-doped, cyanide-grafted graphite phase carbon nitride material prepared in the present invention. DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0043] As described in the background technology, the current industrial production of hydrogen peroxide is mainly through large-scale centralized anthraquinone cycle method. The problem with this method is that its energy comes from fossil fuels, which will emit a large amount of carbon dioxide and produce a lot of organic waste and by-products. Generally, the photocatalytic redox reaction uses semiconductors as catalysts and light as energy to reduce oxygen to produce hydrogen peroxide or oxidize water to produce hydrogen peroxide. Therefore, photocatalytic technology, as an efficient, safe and environmentally friendly environmental purification technology, has been recognized by the international academic community for improving indoor air quality.

[0044] Therefore, the present invention proposes a K / O co-doped, cyano-grafted graphite phase carbon nitride material and a preparation method thereof, which will now be further described in conjunction with the accompanying drawings and specific implementation methods.

[0045] In the following embodiments, the raw materials used include: urea, potassium hydroxide and deionized water.

[0046] The equipment used included: beaker for mixing, crucible, magnetic stirrer, forced air drying oven, muffle furnace, transmission electron microscope and UV-visible spectrophotometer.

[0047] Example 1

[0048] A method for preparing a K / O co-doped, cyano-grafted graphite phase carbon nitride material, comprising the following steps:

[0049] (1) 30 mL of deionized water was measured, 15 g of urea powder was added, and after fully dissolved, 0.3 g of potassium hydroxide was added and stirred at room temperature for 20 min (the speed was controlled at 500 r / min), and the mixture was fully mixed to prepare a first mixed solution;

[0050] (2) transferring the first mixed solution to a 100 mL crucible and placing it in a blast drying oven, sealing it with dust-free paper to control the evaporation rate, drying at 80° C. for 16 h, and cooling it to room temperature to prepare a first solid mixture;

[0051] (3) placing the first solid mixture of step (2) in a muffle furnace, heating the mixture to 550° C. at a heating rate of 8.8° C. / min and keeping the temperature for 2 h, cooling the mixture in the muffle furnace to 500° C. for 1 h, keeping the temperature at 500° C. for 2 h, and naturally cooling the mixture to room temperature to prepare a second solid mixture;

[0052] (4) washing the second solid mixture by centrifugation with deionized water to obtain a precipitate;

[0053] (5) The precipitate obtained in step (4) is dried at 80° C. for 12 h, i.e., a K / O co-doped, cyanide-grafted graphite-phase carbon nitride material.

[0054] Example 2

[0055] A method for preparing a K / O co-doped, cyano-grafted graphite phase carbon nitride material is carried out according to Example 1, except that:

[0056] In step (1), the amount of potassium hydroxide added is 0.5 g.

[0057] Example 3

[0058] A method for preparing a K / O co-doped, cyano-grafted graphite phase carbon nitride material is carried out according to Example 1, except that:

[0059] In step (1), the amount of potassium hydroxide added is 0.7 g.

[0060] Comparative Example 1

[0061] The preparation method of graphite phase carbon nitride material comprises the following steps:

[0062] 15 g of urea powder was placed in a muffle furnace, heated to 550° C. at a heating rate of 8.8° C. / min and kept warm for 2 h, cooled to 500° C. in the muffle furnace for 1 h, then kept warm at 500° C. for 2 h, and naturally cooled to room temperature to prepare a first solid mixture, i.e., a graphite phase carbon nitride material.

[0063] Performance Testing

[0064] 1. The K / O co-doped, cyano-grafted graphite phase carbon nitride material prepared in Example 2 was observed under a transmission electron microscope. The results are as follows: Figure 1 As shown in the figure, it can be seen that the prepared K / O co-doped, cyanide-grafted graphite phase carbon nitride material still maintains a lamellar structure. Compared with carbon nitride nanosheets, the K / O co-doped, cyanide-grafted graphite phase carbon nitride material has a higher photocatalytic hydrogen peroxide production efficiency under visible light, which effectively improves the utilization rate of sunlight.

[0065] 2. Take 5 mg of the material obtained in Examples 1-3 and Comparative Example 1 and dissolve it in 30 mL of water (containing 10% isopropanol). Under the condition of continuous oxygen bubbling, dark treatment was carried out for 30 minutes to achieve oxygen adsorption equilibrium. After illumination, 1.5 mL of the sample was taken every 10 minutes, and 0.5 mL of 0.1 M potassium hydrogen phthalate solution and 0.5 mL of 0.4 M potassium iodide solution were added. After standing for 30 minutes, the absorbance at 350 nm was measured by ultraviolet spectrophotometer.

[0066] The changes in the amount of hydrogen peroxide produced by the materials obtained in Examples 1-3 and Comparative Example 1 under LED visible light and time are shown in FIG. Figure 2 ,pass Figure 2 It can be seen that the photocatalytic hydrogen peroxide production of the product obtained in Example 2 when the amount of potassium hydroxide added was 0.5 g was the highest, which was 6.5 times that of the original carbon nitride nanosheets.

[0067] 3. The rate of change of the photocatalytic production of hydrogen peroxide by the materials obtained in Examples 1-3 and Comparative Example 1 under LED visible light with time is shown in FIG. Figure 3 ,pass Figure 3 It can be seen that when the amount of potassium hydroxide added in Example 2 is 0.5 g, the photocatalytic hydrogen peroxide production rate of the product obtained is the highest, which is 6.5 times that of the carbon nitride nanosheets.

[0068] Active site analysis

[0069] pass Figure 4 The photocatalytic active sites of hydrogen peroxide production in K / O co-doped and cyanide-grafted graphene-phase carbon nitride materials were calculated and determined. Figure 4The O site shows that it has the lowest O2 adsorption energy (-1.60 eV), indicating that the O site is more conducive to the adsorption and activation of O2 to promote the photocatalytic H2O2 production. Since the O site is due to the interaction between potassium metal and urea precursor, the oxygen atoms in the urea molecule are incorporated into the carbon nitride skeleton. Therefore, the addition of different amounts of KOH leads to different active sites of K / O co-doped and cyano-grafted graphite phase carbon nitride materials. The different number of active sites also leads to differences in the photocatalytic performance of K / O co-doped and cyano-grafted graphite phase carbon nitride materials.

[0070] Table 1 shows the changes in the amount of hydrogen peroxide produced by the K / O co-doped, cyanide-grafted graphite-phase carbon nitride materials prepared in Examples 1, 2, and 3 under LED visible light and time.

[0071] Table 1

[0072]

[0073] It can be seen from Table 1 that when the amount of potassium hydroxide added in Example 2 is 0.5 g, the photocatalytic hydrogen peroxide production rate of the product obtained is the highest, and the number and concentration of active sites are optimal.

[0074] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A K / O co-doped, cyanide-grafted graphite-phase carbon nitride material, wherein the microscopic morphology of the graphite-phase carbon nitride material is a lamellar structure, K ions form KN bridges between lamellar layers, oxygen replaces the CN=C bond in the triazine skeleton to form a COC bond, and the amino group at the edge of the carbon nitride is protonated to generate a cyanide group.

2. The method for preparing the K / O co-doped, cyano-grafted graphite phase carbon nitride material according to claim 1 comprises the following steps: (1) adding urea to deionized water and stirring to dissolve, then adding potassium hydroxide and stirring to prepare a first mixed solution; (2) drying the first mixed solution of step (1) and cooling it to room temperature to prepare a first solid mixture; (3) calcining and cooling the solid mixture obtained in step (2) to room temperature to obtain a second solid mixture; (4) Washing the second solid mixture in step (3) with water, and then drying the precipitate after centrifugal washing to obtain a K / O co-doped, cyanide-grafted graphite phase carbon nitride material.

3. The preparation method according to claim 2, characterized in that: In step (1), the mass volume ratio of urea to deionized water is (10-20):30, in units of g / mL.

4. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of urea to potassium hydroxide is (10-20):(0.3-1).

5. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of urea to potassium hydroxide is (10-20):(0.3-0.7).

6. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of urea to potassium hydroxide is (10-20):0.

5.

7. The preparation method according to claim 2, characterized in that: In step (2), the drying temperature is 75-85° C. and the drying time is 10-20 h. Before drying, the solution is first transferred to a 100 mL crucible and sealed with dust-free paper to control the evaporation rate of the aqueous solution.

8. The preparation method according to claim 2, characterized in that: In step (3), the calcination is carried out by placing the mixture in a muffle furnace at 500-600° C. for 1-3 hours, cooling the mixture to 450-550° C. for 1-3 hours, and drying the mixture at 75-85° C. for 10-20 hours.

9. Use of the K / O co-doped, cyano-grafted graphite-phase carbon nitride material according to claim 1 in photocatalytic production of hydrogen peroxide.

10. The use according to claim 9, characterized in that: The specific application methods are as follows: With LED as light source, the K / O co-doped and cyano-grafted graphite phase carbon nitride material is added to water containing isopropanol, and dark treatment is performed under the condition of continuous oxygen bubbling to reach oxygen adsorption equilibrium, and then illumination is performed to realize photocatalytic production of hydrogen peroxide; the mass volume ratio of the K / O co-doped and cyano-grafted graphite phase carbon nitride material to the water containing isopropanol is (4-8):30, in units of mg / mL, the mass concentration of isopropanol in the water containing isopropanol is 10%, the dark treatment time is 20-40 minutes, the illumination time is 20-70 minutes, and the light source is ultraviolet light or visible light.

Citation Information

Patent Citations

  • Potassium-phosphorus co-doped graphite phase carbon nitride and preparation method thereof

    CN118454714A

Cited By

  • Layered double hydroxide modified cyano carbon nitride composite material, preparation method and water pollution treatment method

    CN121513938A

  • Layered double hydroxide modified cyanocarbon nitride composite material, preparation method and water pollution treatment method

    CN121513938B

  • Preparation method and application of potassium modified carbon nitride bifunctional photocatalyst

    CN121695908A